Landscape ecology of the capybara (Hydrochoerus hydrochaeris) in the Chaco region of Paraguay - Campos Krauer, Juan Manuel (Kansas State University, 2009)
Habitat fragmentation and destruction are the most ubiquitous and serious environmental threats confronting the long-term survival of plant and animal species worldwide. However, some native or exotic species can take advantages of these alterations and expand their range, placing endemic species at risk of extinction by changing the composition of biotic communities and altering ecosystem. Capybara (Hydrochoerus hydrochaeris) are a widely distributed rodent throughout most of South and Central America, but restricted to areas of standing water. As the Gran Chaco ecosystem of Paraguay has been converted from dry tropical forest to pastureland, I hypothesized that this habitat alteration created potential for invasion by capybara into newly fragmented areas. I used ecological niche modeling to generate hypotheses about how the distribution of capybara has been affected by land use change, and tested those hypotheses with phylogeographic analyses. To understand the mechanisms that have allowed the invasion, I investigated home range, habitat use and thermoregulation of capybara via radiotelemetry in a deforested area in which capybara had recently invaded. Genetic analyses confirm a rapid range expansion scenario with evidence of secondary contact between two distinct phylogroups which had previously been disjunct. Modeling results indicated that conversion of forest to pastureland allowed the expansion to occur. Capybara selected water significantly more than it was available to them, and avoided shrub forest. I found a significant positive correlation between body temperature and distance from water, and a significant negative correlation between distance from water and Chaco ambient temperature. Capybara proximity to water appeared to be tightly linked to body thermoregulation. These results suggest that although capybara have expanded into the Chaco forest as it is converted to pastureland, the presence of permanent water sources in those pastures are the mechanism that allow capybara to persist in this habitat. This is the first study to characterize capybara in a xeric habitat without a year round water source, and scarce natural grasslands. My results show how anthropogenic habitat modification has allowed capybara to thrive. Understanding how capybara invade and utilize the deforested Central Dry Chaco will provide valuable information for the future management of the species and the Chaco ecosystem.
Keywords: Capybara; Gran Chaco; Range expansion; Ecological niche modeling; Phylogeography; Biology, Ecology (0329); Biology, Genetics (0369)